2021
DOI: 10.4236/jbm.2021.910014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Urinary Tract Infections and Associated Risk Factors among Pregnant Women in Enugu Metropolis, Nigeria

Abstract: The prevalence of Urinary Tract Infections (UTI) among pregnant women was carried out in the Department of Obstetrics and Gynaecology of five (5) different hospitals in Enugu metropolis. Four hundred and eighty (480) pregnant women whose ages ranged from 20 -40 years were recruited in this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Although this difference was not statistically significant among the entire study participants (p=0.347), it was statistically significant for participants in GHC, where the prevalence was 30.8% (8/26) in married compared to 24.4% (11/45) in singles (p=0.0280). This is in agreement with the finding of Ezugwu et al, (27) but contradicts Wanja et al, (28) in Kenya, who reported highest prevalence of UTIs among widowed (57.1%). The highest prevalence of UTI among married participants in this study may be attributed to increase in parity or a higher number of pregnancies (27).…”
Section: Risk Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…Although this difference was not statistically significant among the entire study participants (p=0.347), it was statistically significant for participants in GHC, where the prevalence was 30.8% (8/26) in married compared to 24.4% (11/45) in singles (p=0.0280). This is in agreement with the finding of Ezugwu et al, (27) but contradicts Wanja et al, (28) in Kenya, who reported highest prevalence of UTIs among widowed (57.1%). The highest prevalence of UTI among married participants in this study may be attributed to increase in parity or a higher number of pregnancies (27).…”
Section: Risk Factorssupporting
confidence: 92%
“…This is in agreement with the finding of Ezugwu et al, (27) but contradicts Wanja et al, (28) in Kenya, who reported highest prevalence of UTIs among widowed (57.1%). The highest prevalence of UTI among married participants in this study may be attributed to increase in parity or a higher number of pregnancies (27).…”
Section: Risk Factorssupporting
confidence: 92%
“…Escherichia coli was the most frequently isolated organism with a prevalence of 53.4% (111 samples) while other pathogens accounted for 46.6% (89 samples). These values are slightly higher to the findings of previous research among pregnant women in the Enugu metropolis which reported an coli prevalence of 40.6% (89 samples) while other pathogens accounted for 59.4%(295 samples) [25]. Our findings also varies with the findings of some studies which reported an overall prevalence of 25.3% for pregnant women with asymptomatic UTI as against 5.0% recorded in the present study as well as Klebsiella pneumonia (45%) reported as the most frequently isolated organism compared to E. coli (53.4%) which was the most frequently isolated organism in the present study [26].…”
Section: Discussioncontrasting
confidence: 80%
“…This is in agreement with Ezugwu et al . [27] but contradict Wanja et al . [28] in Kenya, who reported highest prevalence of UTIs among widowed (57.1%).…”
Section: Discussionmentioning
confidence: 86%